EXTH-58. ONCOSCILLATORS: INDUCTION OF THE MITOCHONDRIAL PERMEABILITY TRANSITION IN CANCER CELLS - Sharpe, Martyn (Neuro Oncol, 2020)
Magnetic fields in the mT range influence spin state pairing in redox-active radical pairs generating spin-forbidden quantum states which are kinetically inert. Studies examining the effects of static magnetic fields on mitochondrial electron transfer kinetics have demonstrated only modest effects. When neodymium super-magnets are securely attached to and precision-balanced on the shafts of electronically-controlled motors it is possible to generate rotating magnetic fields of desirable strengths and frequencies. Unlike a static magnetic field or an alternating field in a static electromagnetic coil, oscillating magnetic field (OMF) produced by rotating lines of force of a spinning permanent magnet can dynamically couple the electron spins of radical pairs within proteins whose orientations are ‘fixed’. The frequencies of rotation of magnets can also be tuned to appropriate electron cycling resonances within the proteins. Using OMF of appropriate field strength, frequency and on/off acceleration/deceleration profiles we can completely arrest electron transport in isolated respiring rat liver mitochondria. Parallel to this inhibition of electron flux, we also independently observe an increase in superoxide and hydrogen peroxide. Under certain OMF exposure regimes, we observe membrane permeability transition in these mitochondria when using succinate as substrate, and show that the mitochondrial membrane permeability transition effect can be blocked by bongkrekic acid. We have examined the effect of OMF on oxygen consumption in cultured primary cancer cells with a rotating magnet (oncoscillator) that is an integral component of a new anti-cancer Oncomagnetic device. We observe three main effects in addition to the inhibition of respiratory flux in cancer cells – damage to the respiratory complex, uncoupling and generation of superoxide/hydrogen peroxide. OMF generated by oncoscillators can induce mitochondrial permeability transition in primary cultured malignant meningioma, diffuse intrinsic pontine glioma and GBM cells. Parallel experiments with normal human astrocytes show only minor changes in cellular/mitochondrial function under these conditions.